The rocky road of interregionalism: EU sanctions against human rights-violating Myanmar and repercussions on ASEAN–EU relations*. Issue 3 (2nd July 2016) - Schembera, Kerstin
Abstract: From 1991 until 2012, the European Union (EU) applied sanctions on Myanmar with the purpose of promoting democracy and human rights. In addition, the EU called on the Association of Southeast Asian Nations (ASEAN) to exert pressure on Myanmar. This paper analyses, in the context of Myanmar's 1997 accession to ASEAN, how the EU's sanctions approach towards Myanmar was perceived within ASEAN and related repercussions of this approach on ASEAN–EU interregional relations. With the accession of Myanmar as the base story, it is argued that a regional organizations membership concept implies specific dealings with normative ideas such as democracy and human rights as well as strategies of punishment such as sanctions. The differing membership concepts of ASEAN and the EU explain ASEAN's critical perception of the EU's sanctions on Myanmar. Further, the conceptual difference in membership also explains that the EU's pressure on ASEAN has severely impaired the interregional relations.